PWE-060 Is a false positive faecal calprotectin as false as you think?. (22nd June 2015) - Alzoubaidi, D; Asser, L; Price, T; Lithgo, K; Housley, D; Johnson, MW
Abstract : Introduction: There is a clear need for a simple unambiguous test to differentiate between functional and true organic disease. This would have the effect of reducing the number of unnecessary investigations such as colonoscopies, whist reducing health service costs. Faecal calprotectin is a well validated non-invasive faecal inflammatory marker capable of differentiating functional (e.g. Irritable Bowel Syndrome) from organic (e.g. Inflammatory Bowel Disease). A recent BMJ meta-analysis suggested that it had 93% sensitivity and 96% specificity, with a false positive rate of 9%. The false positives were labelled as patients with a high faecal calprotectin who had subsequently undergone normal gastroscopy and colonoscopy. We decided to investigate this further. Method: All the patients who had undergone a small bowel capsular endoscopy in our unit from 2011 to 2014 were indentified. Patients with an unexplained positive faecal calprotectin were selected (regardless of their referral indication). A retrospective analysis of the capsule findings was then made in those patients who had undergone normal endoscopic investigation. We excluded those with a positive endoscopy. This left us with 21 patients with a positive faecal calprotectin who had negative endoscopies. Results: A total of 206 patients underwent capsule endoscopy between 2011 and 2014. Of these 46 had raised faecal calprotectin levels. 160 were excluded because of positive endoscopic findings. This lead to a total of 21 patients with raised faecal calprotectin and normal endoscopic investigations, labelled as false positives. Within this group 71.4% were found to have small bowel pathology including 12 (57.14%) patients with enteropathy, 2 (9.52%) patients had angiodysplasia and 1 (4.76%) with small bowel malignancy. Conclusion: The documented false positive rate of 9% may not be as accurate as we previously thought. In our unit capsule endoscopy highlighted a pathological explanation in 71.4% and possible small bowel Crohn's Disease in 57.14% of patients. Disclosure of interest: None Declared. Reference: van Rheenen PF, Van de Vijver E, Fidler V. Faecal calprotectin for screening of patients with suspected inflammatory bowel disease: diagnostic meta-analysis. BMJ. 2010;341 :c3369